PENGARUH PEMBERIAN KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KINERJA GURU DAN KARYAWAN SMK MUHAMMADIYAH WANASARI KABUPATEN BREBES - Sri Rahayu (Jurnal Strategik, 2017)
ABSTRACT The objectives of this study include: To determine the effect of financial and non-financial compensation on the performance of teachers and employees of the Muhammadiyah Wanasari Vocational School in Brebes Regency. The research method used is a case study, while for data analysis using statistical analysis tools, namely: (1) Validity test, (2) reliability test, (3) normality test (4) multicollinearity test, (5) heteroscedasticity test, (6) -T Test, (7) -F Test. The results showed that financial compensation had a positive and significant effect on the performance of teachers and employees. This can be seen from the value of t count> t table (6.207> 1,703) and the significance value 1,703) and the significance value 2.920) and the significance value